2005
DOI: 10.1007/11428862_23
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Reservations from the Grid on Planning-Based Resource Management

Abstract: Abstract. Advance Reservations are an important concept to support QoS and Workflow Scheduling in Grid environments. However, the impact of reservations from the Grid on the performance of local schedulers is not yet known. Using discrete event simulations we evaluate the impact of reservations on planning-based resource management of standard batch jobs. Our simulations are based on a real trace from the parallel workload archive. By introducing a new option for scheduling reservations in planning-based resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…It's also shown that a limited number of additional AR from the Grid had only a limited impact on the performance of local batch jobs. As in [3], specific local scheduling algorithms were not mentioned in [4].…”
Section: Related Workmentioning
confidence: 93%
See 2 more Smart Citations
“…It's also shown that a limited number of additional AR from the Grid had only a limited impact on the performance of local batch jobs. As in [3], specific local scheduling algorithms were not mentioned in [4].…”
Section: Related Workmentioning
confidence: 93%
“…Experiment were carried out with the Maui scheduler and a trace file of an actual workload, but the specific scheduling parallel scheduling algorithms used were not mentioned in that paper. The impact of advance reservation on planning-based resource management of standard batch jobs was evaluated in [4] by using discrete event simulations. It's also shown that a limited number of additional AR from the Grid had only a limited impact on the performance of local batch jobs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Heine et.al. showed that by using a native planning based resource management system instead of an enhanced queuing based, the impact of the advance reservations is less dramatic [6]. In [7] a comprehensive overview on resource management systems supporting advance reservation is given.…”
Section: Introductionmentioning
confidence: 99%
“…The development of scheduling strategies for MPP systems is based on workload traces originating from real installations, see for example Heine et al [16]. Such workload data include all hidden job dependencies, patterns and feedback mechanisms.…”
Section: Introductionmentioning
confidence: 99%